Flexural strengthening of reinforced concrete beams with CFRP laminates and spike anchors - Assad, Maha (2024)
Carbon fiber-reinforced polymers (CFRP) are widely used to strengthen reinforced concrete (RC) beams. Its major drawback is the brittle failure mode in the form of debonding of the CFRP laminate. The use of CFRP spike anchors demonstrated positive outcomes in mitigating the debonding failure in small-scale concrete prisms in previous studies. However, the real-life behavior of anchored RC beams was rarely studied . This study aims to investigate the flexural behavior of externally strengthened RC beams with CFRP laminates and anchored at end with CFRP spike anchors. The results of anchored beams was compared with unanchored specimens in terms of load-deflection response, strain in the FRP laminates, and failure modes. Results showed that anchorage of CFRP laminates with CFRP splay anchors positively affected the flexural capacity of the specimens. An average increase in the load-carrying capacity of 19 % was portrayed in the anchored specimens compared to the unanchored specimen. Anchorage of FRP laminates resulted in the mitigation of debonding failure and thus, enhanced strain utilization in laminates. A considerable improvement in strain utilization is exhibited by the specimen anchored with two anchors at each end. Moreover, increasing the anchor's dowel diameter significantly improved the load-carrying capacity but lowered the ultimate strain reached in the laminate. Results indicated that larger diameter anchors provide strengthening effect similar to increasing the number of FRP layers instead of providing anchorage to the FRP sheet. This is primarily due to the increase in the fan length and thickness as the anchor's dowel diameter increases.